Impact of conditional cash transfer scheme (MAMATA) on the prevalent MCH care practices in rural areas of Ganjam district, Orissa: a descriptive study - Ali, Syed Irfan; Begum, Jarina; Panda, Manasee (International Journal Of Community Medicine And Public Health, 2018)
Background: RMNCH services are provided in an integrated manner to it’s beneficiaries under the premise of Primary Health Care. The utilization rates for such services have remained abysmally low and stagnated over the years. The problem lies in failure to generate a demand for such services among it’s beneficiaries. MAMATA a conditional cash transfer scheme implemented in Odisha, aims to bring around radical changes by addressing the issue of demand generation. The objectives of the study were to assess the implementation of MAMATA scheme services in the study area and to assess the impact made by the scheme in their life. Methods: The study was conducted on 200 women, who were randomly selected from the 903 pregnant women registered under Mamata Scheme from a randomly selected block of Odisha. They were then followed up for a period of 15 months. Results: Implementation of the scheme in the district was smooth, the instalments were paid regularly in most of the cases without any delay. Impact of the scheme- 98% got adequate rest during pregnancy, because of the scheme. 95% utilized the money for purchasing nutritious food and procuring medicines. The scheme has also helped develop a health seeking attitude in most of the beneficiaries (85%). 97% felt a sense of empowerment and independence compared to the past. Conclusions: The benefits of MAMATA scheme percolated beyond the boundaries of demand generation. It also brought about a sense of empowerment and independence among it’s beneficiaries.